If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13(9x + -6) = 6x + -4 Reorder the terms: 13(-6 + 9x) = 6x + -4 (-6 * 13 + 9x * 13) = 6x + -4 (-78 + 117x) = 6x + -4 Reorder the terms: -78 + 117x = -4 + 6x Solving -78 + 117x = -4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -78 + 117x + -6x = -4 + 6x + -6x Combine like terms: 117x + -6x = 111x -78 + 111x = -4 + 6x + -6x Combine like terms: 6x + -6x = 0 -78 + 111x = -4 + 0 -78 + 111x = -4 Add '78' to each side of the equation. -78 + 78 + 111x = -4 + 78 Combine like terms: -78 + 78 = 0 0 + 111x = -4 + 78 111x = -4 + 78 Combine like terms: -4 + 78 = 74 111x = 74 Divide each side by '111'. x = 0.6666666667 Simplifying x = 0.6666666667
| w+1.2=16.2 | | 12.12=3v | | (4x-5y+3z)+(-4x+5y+3z)= | | 2(3R-2)=4(R+4) | | -139-2x=57-9x | | 15+4x=7x+48 | | 12-(x-12)=4 | | 3(1-3x)=-8g+14 | | -2(5+5x)=-120 | | 20=3x-x+6 | | -3(7x+4)=-12 | | -7=5x+7x-7 | | 12-3(2x+1)=4w-21 | | 35(5)+.08x=25(5)+.25x | | 33xy/3x | | -2x+2-6x=34 | | 3(45)+6x=303 | | 2x+2-6x=34 | | 5n-10=8n-14 | | 12x-3=20x-9 | | 4x-3+2x-x=10 | | 7/9×1/5 | | 6y-19=3y+14 | | 5v-4/10= | | 1/6y=1 | | 15x-10=-9+2x | | (y+7)(y-3)(y+6)= | | 39=22+2x+y | | 18a+6-30= | | 35=20-3 | | 6(3a+1)-30= | | -15=4d+1 |